Kamenge, Northern Quarters - Gerosa, Manu; Munoz, Salva (Italy, 2010)
In a country where democracy is still new and fragile, Alexis Sinduhije sets out to fight for a livable Burundi. An exploration of the troubled past and uncertain future of Burundi.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films